12+6q=13+5q

Simple and best practice solution for 12+6q=13+5q equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12+6q=13+5q equation:


Simplifying
12 + 6q = 13 + 5q

Solving
12 + 6q = 13 + 5q

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '-5q' to each side of the equation.
12 + 6q + -5q = 13 + 5q + -5q

Combine like terms: 6q + -5q = 1q
12 + 1q = 13 + 5q + -5q

Combine like terms: 5q + -5q = 0
12 + 1q = 13 + 0
12 + 1q = 13

Add '-12' to each side of the equation.
12 + -12 + 1q = 13 + -12

Combine like terms: 12 + -12 = 0
0 + 1q = 13 + -12
1q = 13 + -12

Combine like terms: 13 + -12 = 1
1q = 1

Divide each side by '1'.
q = 1

Simplifying
q = 1

See similar equations:

| (2+x)(200-20x)=720 | | 9x-19=98 | | 10/3=1/3 | | 6p+5=53 | | 0=-0.004x^2+x+2.5 | | 400+160x-20x^2=720 | | 21z-3(2z+14)=14z+11 | | 4x+3+6x=17 | | 5(x-9)=4x | | 5x-45=4x | | 4x^4-8x^3+5x^2-x-1=0 | | (4x^3-8x^2+5x-1)=0 | | 8y-9x-1=0 | | 15p+40= | | 5-p=-2 | | -19v-18=-16v+3 | | -19v-18=16v+3 | | 4v^3+6v^2-4v=0 | | 2y^2=32 | | 3x-7=9x+18 | | 2x+10=3x-22 | | 5(3n-1)=80 | | S=35+14t-2t | | rX^2-37x-36=0 | | 7x+1=3x+19 | | 7x-1=3x+19 | | 2x+(x-6)=3x-(4x-6) | | 18=3(25t+2) | | P(4)=x^3-4x^2+8 | | 6=10-2a | | 6x+1=x+7 | | 4=x-0.6 |

Equations solver categories